Interstitial ectopic pregnancy: A rare and difficult clinicosonographic diagnosis - R Rastogi; G L Meena; N Rastogi; V Rastogi (Wolters Kluwer Medknow Publications, 2008)
Ectopic pregnancy in the interstitial part of the fallopian tube is a rare event. This condition presents a challenge for clinical as well as radiological diagnosis. Although routine two-dimensional ultrasound can be suggestive, three-dimensional ultrasound is highly accurate in diagnosis. Hence, the authors report a rare case of interstitial ectopic pregnancy diagnosed preoperatively by three-dimensional ultrasound and managed laparoscopically.